480 ICD AFTER STEMI: WHEN AND HOW FREQUENTLY IS IMPLANTED AND WHICH IS THE RATE OF APPROPRIATE INTERVENTIONS. (15th December 2022) - Pezzato, Andrea; Fabris, Enrico; Gregorio, Caterina; Cittar, Marco; Contessi, Stefano; Carriere, Cosimo; Lardieri, Gerardina; Zecchin, Massimo; Perkan, Andrea; Sinagra, Gianfranco
Abstract: Background: there are limited data of implantable-cardioverter-defibrillator (ICD) implantation after STEMI treated with primary percutaneous coronary intervention (pPCI). This study sought to evaluate when and how frequently is ICD implanted after STEMI, the rate of appropriate ICD-interventions, and the independent predictors of ICD implantation. Methods: We analyzed STEMI patients treated with pPCI at the University Hospital of Trieste, Italy, between January 2010 and December 2019. We cross-matched patients data with those present in the Trieste ICD registry. Results: 1805 consecutive patients treated with pPCI were analyzed. During a median follow-up of 6.7 (IQR 4.3-9.2) years, the probability of ICD implantation at 12 months was 2.3% (95%CI: 1.7-3.1) and it remained stable overtime (at 24 months: 2.5%, 95%CI 2.0-3.5 and at 36 months: 2.6%, 95%CI 2.3-3.8). Mean time before ICD implantation was 35.5 months (95%CI: 34.8-36) . 83.1% of implanted ICD were for primary prevention, and more than half (55%) were implanted in patients with ejection fraction (EF)>35% at the moment of STEMI discharge. During a median follow-up of 5.7 (IQR 3.3-8.3) years after ICD implantation, the probability of appropriate ICD intervention was 9% and 11% after 12 and 24 months respectively. In patients with EF>35% at STEMI discharge (median EF 43%; IQR 40-48), predictors of ICD implantation were male sex, anterior STEMI and troponin peak >100.000 ng/dl. Conclusions: The rate of ICD implantation after pPCI is low, however the rate of appropriate ICD interventions is high. A relevant subgroup of patients received ICD implantation at follow-up despite a non-severe EF at discharge after STEMI. Among these patients those with high troponin release deserve strict follow-up and full optimal medical treatment.